Technology of Pesticides and Fertilizers Application with Unmanned Aerial Vehicles in Digital Agriculture - L. A. Marchenko; A. A. Artushin; I. S. Smirnov; T. V. Mochkova; A. Yu. Spiridonov; R. K. Kurbanov (Сельскохозяйственные машины и технологии)
Digital agriculture predetermines the development of robotic agricultural technologies for the application of pesticides and fertilizers using unmanned aerial systems, which are based on unmanned aerial vehicles (UAVs) with a certain working load for monitoring agricultural land and applying agrochemicals. (Research purpose) To develop a technology for variable-rate application of pesticides and fertilizers using unmanned aerial vehicles in digital agriculture. (Materials and methods) In the process of study, the authors used the methodological recommendations on the application of chemicals in the precision farming system (offered by VIM), as well as the normative and technical documentation for unmanned aircraft systems. (Results and discussion) It was shown that the developed technology includes the sequential execution of information and technological operations in off-line and on-line modes. It was found that the application rate of the liquid pesticides of 10-20 liters per hectare reduces losses due to drift from the treatment area and ensures the highest productivity of pesticide application using unmanned aerial vehicles. It was determined that the field processing performance increases as the run length increases, and decreases with the increasing flow rate of the liquid chemical. The rational run length was established to equal 0.8-3.2 kilometers. The authors established requirements for the spraying quality of unmanned aerial vehicles. It was proved that to increase the productivity of unmanned aerial vehicles during plant top-dressing, it is necessary to use unmanned aerial vehicles with a larger working load of 300-400 kilograms. (Conclusions) The authors have developed a technology for variable-rate application of pesticides and fertilizers using unmanned aerial vehicles, algorithms for preparing them for flight, monitoring agricultural lands, making a field orthophotomap, electronic maps of vegetation indices, the phytosanitary status of crops, and variable-rate application of pesticides and fertilizers.